A session by session guide to life story work : a practical resource to use with looked after or adopted children - Shotton, Gillian (Abingdon, Oxon ; New York, NY : Routledge, 2021)
"Life story work is a term often used to describe an approach that helps looked after and adopted children to talk and learn about their life experiences with the help of a trusted adult. This book is an essential step-by-step guide for carers and professionals seeking to carry out life story work with a traumatised or vulnerable child in their care. Underpinned by positive psychology and drawing on up-to-date research and real-life practice, the book offers a sound theoretical understanding of life story work as well as a practical and easy-to-use ten-session programme. Each session covers the equipment and information needed, a consideration of who is best placed to carry out the work, and answers to commonly raised questions. Also discussed are age-appropriate approaches and ideas for extending each session into other activities and methods to make it more feasible for life story work to be a shared activity between two or three adults who know the child well. This book gives professionals and carers the confidence to carry out life story work in a way that is sensitive to the child's needs and positive for their self-perception and relationships"--
A narrative approach to life story work -- Research around the effectiveness of using a narrative approach -- How to use this book -- Session one : establishing the ground rules and feelings cards -- Session two : the tree of life (part A) -- Session three : the tree of life (part B) -- Session four : a map of all the places you have lived -- Session five : birth certificate -- Sessions six and seven : co-constructing the story so far -- Session eight : stones in a jar, acknowledging different types of memories -- Session nine : origami hearts : celebrating people who have had a positive impact -- Session ten : the team of life, part 1 : values -- Session eleven : team of life part 2 : identifying their team and goals -- Session twelve : team of life part 3 : tackling problems -- Session thirteen : therapeutic stories.
"A Speechmark Book" -- cover.
OCLC-licensed vendor bibliographic record.
Keywords: Adopted children -- Psychology -- Handbooks, manuals, etc; Narrative therapy -- Handbooks, manuals, etc; Autobiography -- Therapeutic use -- Handbooks, manuals, etc; Psychic trauma in children -- Treatment -- Handbooks, manuals, etc; Children -- Institutional care; Social work with children; EDUCATION / General